2007
DOI: 10.1007/s00335-007-9056-y
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of BAC transgene copy number in mice: transgene copy number variation across multiple transgenic lines and correlations with transgene integrity and expression

Abstract: Bacterial artificial chromosomes (BACs) are excellent tools for manipulating large DNA fragments and, as a result, are increasingly utilized to engineer transgenic mice by pronuclear injection. The demand for BAC transgenic mice underscores the need for careful inspection of BAC integrity and fidelity following transgenesis, which may be crucial for interpreting transgene function. Thus, it is imperative that reliable methods for assessing these parameters are available. However, there are limited data regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 22 publications
10
129
0
Order By: Relevance
“…To examine the copy number of the transgene, genomic DNA was prepared from early passage mouse embryonic fibroblasts (MEFs) derived from the p16-luc mice. The DNA sequence specific to this human chromosome segment was amplified and quantified by real-time PCR analysis (Ballester et al, 2004;Chandler et al, 2007) using genomic DNA prepared from the same number of early passage human diploid fibroblasts (HDFs) as a control. The signals obtained from the p16-luc MEFs were almost half compared with those from HDFs, which have two copies of the human Ink4a/Arf gene (Fig.…”
Section: Expression In Living Animalsmentioning
confidence: 99%
“…To examine the copy number of the transgene, genomic DNA was prepared from early passage mouse embryonic fibroblasts (MEFs) derived from the p16-luc mice. The DNA sequence specific to this human chromosome segment was amplified and quantified by real-time PCR analysis (Ballester et al, 2004;Chandler et al, 2007) using genomic DNA prepared from the same number of early passage human diploid fibroblasts (HDFs) as a control. The signals obtained from the p16-luc MEFs were almost half compared with those from HDFs, which have two copies of the human Ink4a/Arf gene (Fig.…”
Section: Expression In Living Animalsmentioning
confidence: 99%
“…High copy number tandem integration is thought to lead to transgene silencing (Tang et al, 2007), and high copy numbers may decrease in aging transgenic animals. A previous study showed that at least approximately 10 copies were ideal for analysis (Chandler et al, 2007). In our study, 12 copies of the GH transgene ensure GH expression in transgenic goats.…”
Section: Discussionmentioning
confidence: 60%
“…We generated several transgenic goat lines by SCNT using the pcGH construct. Because the GH transgenic line was not generated by site-specific recombination technology, the integration sites and copy numbers were uncertain, and these factors may influence the phenotype of transgenic animals (Chandler et al, 2007). Recently, because less DNA is required and because of its high sensitivity, precision, and repeatability, quantitative PCR has replaced Southern blotting for determining copy number in transgenic animals (Ballester et al, 2004;Lipinski et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The positional transgenesis approach, knock-in, inserts transgene into mouse genome at a specific location, such as Rosa26 and HPRT locus, while random transgenesis, which usually uses bacterial artificial chromosome (BAC), integrates the transgene at a random location. These days, the BAC transgenic approach has been widely used owing to its advantages, including ease of use and the availability of large library [32][33][34][35][36][37]. However, endogenous gene expression can be altered because the delivery of BAC may contain coding regions or promoters of other genes [20,38].…”
Section: Genetic Identitymentioning
confidence: 99%